RISK FACTORS FOR FALLS IN CATARACT PATIENTS AWAITING SURGERY. (7th October 2012) - Fraser, M; Meuleners, L; Lee, A; Ng, J; Morlet, N
Abstract : Background: Poor vision is a risk factor for falls among older adults. Unfortunately, in Western Australia (WA), cataract patients in the public health system can wait one year to 18 months for first eye surgery. It would be useful to determine risk factors for falls during this period. Aims/Objectives/Purpose: To determine visual and other risk factors for falls among bilateral cataract patients awaiting first eye surgery in WA. Methods: Ninety nine drivers aged 55 years and older with bilateral cataract were recruited from three public hospitals in WA. Self-reported data on all falls during the previous 12 months was collected during the week before first eye cataract surgery. Visual measures including visual acuity, contrast sensitivity and stereopsis were assessed and cognitive tests administered. Age, gender, health conditions and living situation data was also collected. A logistic regression model was used to determine visual and other risk factors for falls. Results/Outcomes: During the year before surgery, 29.3% of patients had at least one fall. Visual acuity in the better eye was the only visual measure associated with increased risk of a fall (p=0.038). Those with more co-morbid conditions were also at increased risk (p=0.005). Interestingly, increasing age was associated with decreased risk of a fall (p=0.020) as was living with others (p=0.036). Significance/Contribution to the field: The better eye visual acuity measure could be used by clinicians to identify and possibly prioritise patients at risk of falls while waiting for cataract surgery.